Co-simulation analysis of the single stage screw feedback digital hydraulic cylinder. (September 2020) - Ma, Changlin; Hao, Lin; Gao, Yunguang; Han, Yangyang
Abstract: Taking the single-stage spiral feedback digital hydraulic cylinder as the research object, on the basis of analyzing its composition and mechanical feedback mechanism, we explored the idea of collaborative simulation based on AMESim and Simulink software, and finally realized the collaborative simulation of digital hydraulic cylinder. In this simulation, we use AMESim software to build the mechanical and hydraulic models, Simulink software to build the step-in motor model, and integrate the hydraulic model into the Simulink platform environment through the software interface. We can easily change the parameters to analyze its performance, and provide a convenient way for digital hydraulic cylinder performance optimization research.